Effects of general and sexual minority-specific COVID-19-related stressors on the mental health of lesbian, gay, and bisexual people in Hong Kong - Suen, Yiu Tung (Psychiatry Res, 2020)
The impact of COVID-19 on mental health has begun to be widely recognized, but there is an absence of studies on how the mental health of lesbian, gay, and bisexual (LGB) people have been affected by the COVID-19 pandemic. A total of 857 LGB people in Hong Kong participated in a community-based survey study. Over one-fourth of them met the criteria for probable clinical depression (31.5%) and generalized anxiety disorder (27.9%). Besides general stressors, we identified sexual minority-specific stressors during the pandemic. 4.2% of the participants indicated that they had frequently experienced family conflict related to sexual orientation. One-third responded that they had largely reduced connection to the lesbian, gay, bisexual, and transgender plus (LGBT+) community (34.7%). The results showed that sexual minority-specific COVID-19-related stressors explained significant variance in depressive and anxiety symptoms, above and beyond the contribution of general COVID-19-related stressors. Since LGB people are particularly vulnerable to poor mental health during the COVID-19 pandemic, LGB people-targeting organizations need to understand more about family, space, and privacy concerns in order to provide better support, and LGB safe spaces and shelters may be needed as a policy response.